In Silico Screening and Molecular Dynamics Simulations against Tyrosine-protein Kinase Fyn Reveal Potential Novel Therapeutic Candidates for Bovine Papillomatosis - Barros, Gerlane S.; Barreto, Débora Machado; Cavalcanti, Sandy G. S.; Oliveira, Tiago Branquinho; Rodrigues, Ricardo Pereira; de Aragão Batista, Marcus Vinicius (Current Medicinal Chemistry, 2024)
Background: Decreased beef productivity due to papillomatosis has led to the development and identification of novel targets and molecules to treat the disease. Protein kinases are promising targets for the design of numerous chemotherapy drugs. Objective: This study aimed to screen and design new inhibitors of bovine Fyn, a protein kinase, using structure-based computational methods, such as molecular docking and molecular dynamics simulation (MDS). Methods: To carry out the molecular docking analysis, five ligands obtained through structural similarity between active compounds along with the cross-inhibition function between the ChEMBL and Drugbank databases were used. Molecular modeling was performed, and the generated models were validated using PROCHECK and Verify 3D. Molecular docking was performed using Autodock Vina. The complexes formed between Fyn and the three best ligands had their stability assessed by MDS. In these simulations, the complexes were stabilized for 100 ns in relation to a pressure of 1 atm, with an average temperature of 300 k and a potential energy of 1,145,336 kJ/m converged in 997 steps. Results: Docking analyses showed that all selected ligands had a high binding affinity with Fyn and presented hydrogen bonds at important active sites. MDS results support the docking results, as the ligand showed similar and stable interactions with amino acids present at the binding site of the protein. In all simulations, sorafenib obtained the best results of interaction with the bovine Fyn. Conclusion: The results highlight the identification of possible bovine Fyn inhibitors; however, further studies are important to confirm these results experimentally.
Keywords: virtual screening